Evaluating the status of theories of emotion in political science and psychology - Marcus, George E. (Frontiers in Political Science, 2023)
Emotion is an increasingly influential area of research in psychology, political psychology, political science, and other social sciences. Research is best when driven by theory because the absence of theory generates research that can lack coherence and precision of language and meaning from one study to another, from one program of research to another. In brief, a theory provides essential binding foundations that enable scientific explanations to be rigorously tested. Furthermore, reliance on incomplete or unsound theories tends to generate flawed results. I evaluate four current emotion research programs to assess whether each constitutes a comprehensive theory of emotion. The programs under consideration, in alphabetical order, are appraisal theories in psychology and in political science, emotion regulation, and valence-based accounts. A review of the elements that constitute a theory of emotion of each of these programs persuades me that each has weaknesses that should be addressed. In sum, I find that the ambition to have a comprehensive theory of emotion awaits fulfillment.